2012
DOI: 10.1111/j.1442-1984.2012.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pollination characteristics between the insular shrub Clerodendrum izuinsulare and its widespread congener C. trichotomum

Abstract: Impact of pollinator shift on differentiation of floral morphology has attracted the interest of naturalists for many years. A comparative investigation was conducted for determining the pollination characteristics, including pollinator assemblage, floral morphology, flowering phenology, and self‐compatibility, of two closely related Clerodendrum species—insular C. izuinsulare and widespread C. trichotomum. Japanese black swallowtail butterflies were the predominant flower visitors in mainland Japan, whereas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Another possible explanation is that pollinator assemblages may vary between the islands. Although pollinators were shared between the plants on both islands, diurnal hawkmoths were predominant on Niijima Island, whereas swallowtail butterflies and nocturnal hawkmoths were infrequently observed (Mizusawa et al, 2014). Carpenter bees (genus Xylocopa ) were also frequently observed on Niijima Island.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation is that pollinator assemblages may vary between the islands. Although pollinators were shared between the plants on both islands, diurnal hawkmoths were predominant on Niijima Island, whereas swallowtail butterflies and nocturnal hawkmoths were infrequently observed (Mizusawa et al, 2014). Carpenter bees (genus Xylocopa ) were also frequently observed on Niijima Island.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, C. izuinsulare is restricted to a limited area in Japan and is also pollinated mainly by lepidopterans. In several areas, the two species occur sympatrically, but no hybrids are found in nature, or even when artificially crossed (Miyake & Inoue, 2003; Mizusawa, Takimoto, Yamasaki, Isagi, & Hasegawa, 2014). They share pollinators, such as swallowtail butterflies, diurnal and nocturnal hawkmoths, and some hymenopterans (Mizusawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the Izu Islands, flowers of some plant species are adapted to limited pollinators. A comparison of pollination strategies of Clerodendrum izuinsulare, which grows only on the Izu Islands, and C. trichotomum, which is widespread on the mainland of Japan as well as on some of the Izu Islands, with respect to Lepidopteran pollinators, has shown that the floral traits (floral morphology and flowering phenology) of C. izuinsulare are adapted to diurnal hawkmoths on the Izu Islands, where the visitation frequency of the original pollinator, swallowtail butterflies, is low (Mizusawa et al 2014). The results obtained for L. auratum in the present study lead almost to a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Pollination systems of plants endemic to the Izu Islands are different from those of their relatives on the mainland. For example, large pollinating insects such as bumblebees and swallowtail butterflies are either absent or rare on the Izu Islands (Inoue 1993;Mizusawa et al 2014). Flowers of Campanula microdonta, which grows on the islands, are much smaller than those of its relative C. punctata, which grows on the mainland.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reasonable to doubt this conclusion given that studies of nocturnal pollination by moths have been especially scarce in Asia (see the review by Johnson et al, ). Moreover, a number of moth flowers have been revealed there over the past few years, including some cases involving hawkmoths (Zhang et al, ; Mizusawa et al, ; Yokota & Yahara, ; Liu & Huang, ; Xiong et al, ; Yan et al, ).…”
Section: Introductionmentioning
confidence: 99%